Organizational Justice and Employee Sustainability: The Mediating Role of Organizational Commitment - Mehreen Fatima; Zeeshan Izhar; Zaheer Abbas Kazmi (SEISENSE Journal of Management, 2020)
Purpose- The primary purpose of the study is to determine the impact of organizational justice (OJ) on employee sustainability. Along with that, it also describes how organizational commitment mediates this direct relationship. This study includes all dimensions of OJ which are distributive, procedural and interactional (interpersonal & informational) within the context of a developing country (Pakistan). Design/Methodology- This study has considered employees working in the banking sector of Pakistan. Two hundred ten questionnaires were received back from employees. Regression analysis was used to analyze direct relationships between variables, while smart partial least squares (PLS) were used for mediation analysis. Findings- Results demonstrated that all hypothesis were accepted and it was also confirmed that organizational commitment (OC) mediates the direct relationship between OJ and employee sustainability (ES). Originality/value- Multidimensional construct of organizational justice was tested in this study, in the context of a developing country (Pakistan), to address the research gap.